ANALISIS ASPEK PERPAJAKAN PADA FINTECH KHUSUSNYA PEER TO PEER (P2P) LENDING UNTUK MENYUSUN ATURAN PERPAJAKAN - Dewi Haptari, Vissia; Aribowo, Irwan (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
Financial technology ('Fintech ') shifts the paradigm of financial transactions and demands more rapid and adaptive change. Based on the results of BBVA's 2017 study, domestic business financing needs will be around IDR 1,600 trillion. In fact, only IDR 600 trillion can be disbursed annually through banks, capital markets and finance companies. Only 11 million of the 60 million SMEs can obtain loans from banks. Sixty percent of that number is based on the island of Java. Indonesia is expected to spend a small and medium business fund of US$ 54 billion by 2020, with more than 57 million micro-businesses proposed bankableThe purpose of this study is to discuss taxation rules as a regulator function and budget function in the fintech  industry specifically the Peer to Peer loan business model (P2P lending ) as part of the fintech  business model. Special licenses related to the transaction and taxation model are also needed to make it easier and can be arranged according to the tax compliance.The government as regulator must issue regulations regarding the development of the P2P lending  industry which includes aspects of taxation, namely subjects, objects, tax rates and collection mechanisms. Development of a special P2P lending  model need to be anticipated quickly because they have to income the state.